The Impact of Self-controlled Attention and Social-comparative Feedback on the Learning of Sandbag Throwing in Adolescents - Seyyed Ahmad Mousavi; Nastaran Parvizi; Rasool Hemayattalab (Shiraz University of Medical Sciences, 2019)
Background: Recent studies have demonstrated that autonomy support, social-comparative feedback, and attentional factors contribute to performance and motor learning skills. The present study investigated the influence of self-controlled attention and social-comparative feedback on the performance and learning of a throwing task. Methods: 80 healthy students of Shahid Khalaj Azad junior high school from Takestan (mean age=14.12 ±0.752 SD) in 2017 academic year, placed in five groups: internal-experimenter-controlled, external-experimenter-controlled, internal-self-controlled, external-self-controlled, and control. Internal groups practiced based on an internal focus of attention, an external group practiced based on an external focus of attention. Experimenter-controlled groups received only veridical feedback, self-controlled groups in addition to the veridical feedback received social-comparative feedback. We used a four (pre-test; acquisition; retention; transfer) × five (groups) repeated measure analyses of variance (ANOVA) in SPSS software version 25 to analyze data. Results: The results indicated that throwing tasks differed significantly between phases. The retention phase score was higher than the other phases (83.14±0.72, P<0.001). Test of between-subjects effects determined that groups significantly differed from each other. The Internal-self-controlled group score was higher in other groups (81.15±6.15, P=0.041). Conclusions: These findings demonstrated that the self-controlled focus of attention in companion with social-comparative feedback enhances motor learning in the first stage of the learning.